2019
DOI: 10.31235/osf.io/aq5xj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Black Protest Events In The Us 1994-2010: Issues, Campaigns And Trends

Abstract: This paper fills a major empirical gap in providing the first systematic data about US Black movement protests between the 1994 and 2010. There is a dearth of systematic information about the Black movement and Black protests between 1995 and its reemergence in Black Lives Matter in 2012. Using a new automated system, we identified 1017 events in 1049 news wire stories relevant to Black protest between 1994 and 2010 from the Annotated English Gigaword file. These data provide insight into Black activism in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The limited explanatory power of our models may be due to theoretical and methodological limitations of the approach we take in this article. While existing social movement theories are largely effective at explaining emergence, they are less effective for studying decline (Davenport 2014; Santoro and Fitzpatrick 2015) and perhaps worse at studying the “doldrums” (Oliver, Hanna, and Lim 2019; Taylor 1989). This may be because movements that are active during protest waves build on previous actions (Koopmans 2004; Tarrow 1998), and such responsiveness makes them conducive for multidecade time-series regressions (often using aggregated counts) like the ones presented here.…”
Section: Discussionmentioning
confidence: 99%
“…The limited explanatory power of our models may be due to theoretical and methodological limitations of the approach we take in this article. While existing social movement theories are largely effective at explaining emergence, they are less effective for studying decline (Davenport 2014; Santoro and Fitzpatrick 2015) and perhaps worse at studying the “doldrums” (Oliver, Hanna, and Lim 2019; Taylor 1989). This may be because movements that are active during protest waves build on previous actions (Koopmans 2004; Tarrow 1998), and such responsiveness makes them conducive for multidecade time-series regressions (often using aggregated counts) like the ones presented here.…”
Section: Discussionmentioning
confidence: 99%
“…Unpunished police violence was also the precipitant for the major riots/insurrections in Miami in 1980 and Los Angeles in 1992. About a third of the Black protest events described in news wire stories concerned unfair policing, including widely covered protests about police killings in New York in the 1990s and again in 2006, and protests and riots after police killings in Cincinnati in 2001and Oakland 2009(Oliver, Hanna, and Lim 2019.…”
Section: Resistance To Repression Before Black Lives Matter Black Movements Against Repressionmentioning
confidence: 99%
“…Taylor (2016 and Fletcher and Rogers (2014) explicitly state that the attack dissipated the Radical Black Congress and Taylor stresses that poll data showed that Blacks had even higher support for profiling Arabs than Whites. Protest event data shows a steep drop in Black protests after 9/11 (Oliver, Hanna, and Lim 2019).…”
Section: Resistance To Repression Before Black Lives Matter Black Movements Against Repressionmentioning
confidence: 99%
See 2 more Smart Citations